The Effect of Read, Cover, Remember, and Retell (RCRR) Strategy on Eighth Semester Students’ Reading Comprehension at English Study Program of Muhammadiyah University of Bengkulu - Yupika Maryansyah; Putri Ramadhani (Fakultas Keguruan dan Ilmu Pendidikan, 2021)
The purpose of this research is to determine the effect of Read, Cover, Remember, and Retell (RCRR) Strategy on studentsâ€™ reading comprehension. This current study was carried out by using quasi experimental method. The subjects of this research were 14 Eight semester students of English Study Program of UMB . The instrument used in this study was a reading comprehension test consisted of pre-test and post-test. Pre-test was given before the treatment and post-test was given after the treatment. The result of the study show that there is an increased scores of students who used RCRR Strategy. After conducting the measuremnet,Â researchers found that T-count value was lower than T-table (1.1904 < 1.70562). However, the total score was 590 and mean score was 84.28 for experimental group, which was higher than the total score in the control group, 555 and mean score was 79.28. This indicate that RCRR has a significant effect on students reading comprehension skill.